Factors that enable and hinder the implementation of projects in the alcohol and other drug field - Sarah MacLean; Lynda Berends; Barbara Hunter; Bridget Roberts; Janette Mugavin (Elsevier, 2012)
Abstract Objective: Few studies systematically explore elements of successful project implementation across a range of alcohol and other drug (AOD) activities. This paper provides an evidence base to inform project implementation in the AOD field. Approach: We accessed records for 127 completed projects funded by the Alcohol, Education and Rehabilitation Foundation from 2002 to 2008. An adapted realist synthesis methodology enabled us to develop categories of enablers and barriers to successful project implementation, and to identify factors statistically associated with successful project implementation, defined as meeting all funding objectives. Thematic analysis of eight case study projects allowed detailed exploration of findings. Results: Nine enabler and 10 barrier categories were identified. Those most frequently reported as both barriers and enablers concerned partnerships with external agencies and communities, staffing and project design. Conclusion: Achieving supportive relationships with partner agencies and communities, employing skilled staff and implementing consumer or participant input mechanisms were statistically associated with successful project implementation. Implications: The framework described here will support development of evidence‐based project funding guidelines and project performance indicators. The study provides evidence that investing project hours and resources to develop robust relationships with project partners and communities, implementing mechanisms for consumer or participant input and attracting skilled staff are legitimate and important activities, not just in themselves but because they potentially influence achievement of project funding objectives.